2021
DOI: 10.1371/journal.pone.0259447
|View full text |Cite
|
Sign up to set email alerts
|

The bioinformatics analysis of RIOX2 gene in lung adenocarcinoma and squamous cell carcinoma

Abstract: Lung cancer is characterized by high morbidity and mortality rates, and it has become an important public health issue worldwide. The occurrence and development of tumors is a multi-gene and multi-stage complex process. As an oncogene, ribosomal oxygenase 2 (RIOX2) has been associated with a variety of cancers. In this article, we analyzed the correlation between RIOX2 expression and methylation in lung cancer based on the databases including the cancer genome atlas (TCGA) (https://portal.gdc.cancer.gov/) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
(35 reference statements)
0
3
0
1
Order By: Relevance
“…It is reported that breast cancer is a highly heterogeneous tumor, and its course of disease evolution has experienced complex biological processes such as multi-gene and multi-stage (101). Additionally, Merino et al (102) found that the occurrence of breast cancer is not only related to the mutation, deletion, or activation of some protooncogenes and tumor-suppressor genes but also related to the inhibition of apoptosis. Actually, the BCL-2 gene involved in cell apoptosis is closely related to the occurrence of breast cancer and the proliferation of breast cancer cells.…”
Section: Bcl-2 and Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that breast cancer is a highly heterogeneous tumor, and its course of disease evolution has experienced complex biological processes such as multi-gene and multi-stage (101). Additionally, Merino et al (102) found that the occurrence of breast cancer is not only related to the mutation, deletion, or activation of some protooncogenes and tumor-suppressor genes but also related to the inhibition of apoptosis. Actually, the BCL-2 gene involved in cell apoptosis is closely related to the occurrence of breast cancer and the proliferation of breast cancer cells.…”
Section: Bcl-2 and Breast Cancermentioning
confidence: 99%
“…Additionally, Merino et al. ( 102 ) found that the occurrence of breast cancer is not only related to the mutation, deletion, or activation of some proto-oncogenes and tumor-suppressor genes but also related to the inhibition of apoptosis. Actually, the BCL-2 gene involved in cell apoptosis is closely related to the occurrence of breast cancer and the proliferation of breast cancer cells.…”
Section: The Role Of the Bcl-2 Family Proteins In Regulating Apoptosi...mentioning
confidence: 99%
“…The incorporation of gene chips with quantitative high-throughput proteomics techniques allows for a powerful and efficient gene sequencing tool for mass-scale analyzing differentially regulated genes between normal and tumorigenic tissues. In a similar manner, from previous examples, the integration of cancer bioinformatics has led to the recent discovery of ribosomal oxygenase 2 (RIOX2) as a key oncogene in lung cancer, which also participates as a common factor in a variety of carcinogenic disturbances [ 221 ]. In another study correlating with lung cancer, bioinformatic analysis was used to identify unique proteomic profiles of patient subtypes associated with sex, response, and tumor progression [ 222 ].…”
Section: The Critical Role Of Bioinformaticsmentioning
confidence: 99%
“…Meme kanserinin oldukça heterojen bir tümör olduğu ve hastalık evrimi sürecinde çok genli ve çok aşamalı gibi karmaşık biyolojik süreçler yaşandığı bilinmektedir (Ilkhomovna, 2021). Ek olarak, (Sun & Zhao, 2021), meme kanseri oluşumunun sadece bazı protoonkojenlerin ve tümör baskılayıcı genlerin mutasyonu, silinmesi veya aktivasyonu ile değil, aynı zamanda apoptozun inhibisyonu ile de ilişkili olduğunu bulmuşlardır. Aslında, hücre apoptozunda yer alan BCL-2 geni, meme kanseri oluşumu ve meme kanseri hücrelerinin çoğalması ile yakından ilişkilidir.…”
Section: Bcl-2 Ve Meme Kanseriunclassified